TRANSFORMASI PERAN GURU PAI DALAM PENGUATAN KARAKTER RELIGIUS PESERTA DIDIK MADRASAH IBTIDAIYAH - Fitriyah Hamzah; Aminullah; Wardhana (Jurnal Diskursus Islam, 2025)
This study aims to identify the forms of transformation in the role of Islamic Religious Education (PAI) teachers at Madrasah Ibtidaiyah (MI) in strengthening students’ religious character. A literature review of various sources and studies produced five key findings: (1) the transformation of PAI teachers functional roles from normative instructors to contextual spiritual facilitators; (2) the use of teacher role-modeling as an effective strategy for character development; (3) the integration of digital technology into religious learning, making it more engaging and relevant to modern learners; (4) the importance of a conducive madrasah environment in supporting Islamic character formation; and (5) the significance of synergy among teachers, school leaders, and parents in cultivating a religious culture. This transformation requires systemic support, including integrative curriculum development, ongoing teacher training, and supportive school policies. The findings affirm that PAI teachers hold a strategic role as moral and spiritual agents in character education for the modern era.